(untitled) (International Journal of Engineering and Computer Science, 2015)
Abstract— Passive Optical Networks are thought to be the next step in the development of Access Networks and providing broadband access in the ”last mile” area. Ethernet PONs (EPON) gain the most attention from the industry as they offer highly flexible, cost effective solution. In this paper we propose algorithms that provide Dynamic Bandwidth Allocation and shift the burden of queue management from the customer to the network, this results in less complicated and more generic equipment used on the customer’s premises. We show the results of simulations to validate the effectiveness of algorithms presented.